Recognizing Average Associates - Allen F. Wysocki; Karl W. Kepner; Derek Farnsworth; Jennifer Clark (EDIS, 2019)
This document outlines a managerial process to ensure average associates are no longer overlooked. It emphasizes recognizing and motivating typical employees to enhance organizational performance. The authors provide strategies for managers to identify and support these associates, fostering a more inclusive and productive work environment. The process includes practical steps for implementing recognition programs and feedback mechanisms that cater to the needs of average associates, ultimately benefiting the entire organization. First published June 2001.